Executive Cognitive Dysfunction and ADHD in Cocaine Dependence: Searching for a Common Cognitive Endophenotype for Addictive Disorders - Cunha, Paulo J.; Gonçalves, Priscila D.; Ometto, Mariella; Dos Santos, Bernardo; Nicastri, Sergio; Busatto, Geraldo F.; de Andrade, Arthur G. (Frontiers in Psychiatry, 2013)
Background: Cocaine dependent individuals (CDI) present executive cognitive function (ECF) deficits, but the impact of psychiatric comorbidities such as Attention-Deficit Hyperactivity Disorder (ADHD) on neuropsychological functioning is still poorly understood. The aim of this study was to investigate if CDI with ADHD (CDI+ADHD) would have a distinct pattern of executive functioning when compared with CDI without ADHD (CDI). Methods: we evaluated 101 adults, including 69 cocaine dependent subjects and 32 controls. ECF domains were assessed with Digits Forward (DF), Digits Backward (DB), Stroop Color Word Test (SCWT), the Wisconsin Card Sorting Test (WCST), and the Frontal Assessment Battery (FAB). DSM-IV criteria for ADHD were used for diagnosis and previous ADHD symptoms (in the childhood) were retrospectively assessed by the Wender-Utah Rating Scale (WURS). Results: there were no significant differences between CDI+ADHD, CDI and controls in estimated IQ, socioeconomic background, education (in years) and premorbid IQ (p>0.05). SCWT and WCST scores did not differ across groups. Nevertheless, CDI and CDI+ADHD performed more poorly than controls in total score of the FAB. Also, CDI+ADHD did worse than CDI on DF, DB, Conceptualization/FAB, and Mental flexibility/FAB. We did not find correlations between cocaine use variables and neuropsychological functioning, but previous ADHD symptoms assessed by WURS were negatively associated with DF (p=0.016) and with the total score of the FAB. Conclusion: CDI+TDAH presented more pronounced executive alterations than CDI and CDI exhibited poorer cognitive functioning than controls. Pre-existing ADHD symptoms may have a significant negative impact on executive dysfunction in CDI. It remains to be investigated by future studies if symptoms such as impulsivity or a pre-existing ECF dysfunction could represent underlying cognitive endophenotypes that would substantially increase the risk for acquiring addictive disorders.